Peranan Konselor dalam Penerapan dan Pemupukan Nilai-Nilai Murni Melalui Rogram Konseling Terhadap Remaja di Sekolah: Satu Wadah Terpadu Antara Guru dan Kounselor - Erlina, Nova (Universitas Islam Negeri Raden Intan Lampung, 2014)
This research aims to review the role of counseling toward the development of qamil people. This research will review and understand western caucus perspectives on human research functions on earth based on freud and rogrs theory. The problem is why human life on earth is causing problems especially from the spiritual aspect even though it has often received counseling therapy. Diseases associated with mental disorders such as new rosis, Emotional instability, stress, mental disorders and their compatriots are evidence of a person's need for counseling. The formation of a model that strives for the overall development of the workforce is expected to be practiced to care for clients facing personal problems, the families of the community. This model is expected to become a martial-client mechanism to deal with every problem not only from the spiritual aspect, even form a healthy human, motivated, confident and willing to face all the problems and challenges in human life in the future.